(untitled) (قضايا سياسية, 2023)
The United States is clearly interested in the Palestinian issue. Indeed, an important part of the developments that occurred to that issue, and what it ended up with, came as a result of American policy. The reasons behind this policy are the relationship between American decision-making centres and interest groups with (Israel), which is based on providing support, at the expense of Palestinian rights. As Trump's administration came to office in 2017, it tried to push for the path of ending the Palestinian cause by adopting the deal of the century, recognizing Jerusalem as the capital of Israel, supporting Israel's normalization with Arab countries, and portraying (Israel) as a country that can be relied upon to deal With challenges and security threats. By studying the variables affecting the American policy towards the Palestinian issue, and the most prominent trends that affected the American policy, the paper concludes that the state of Palestinian affairs determines the way the US deals with it and vice versa.